Il Regolamento (UE) n. 1259/2010 sulla legge applicabile al divorzio e alla separazione personale nella recente prassi giurisprudenziale italiana - Falconi, Federica (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
This article offers a brief analysis of the Italian case-law concerning Regulation (EU) No 1259/2010 on the law applicable to divorce and legal separation. Only in a few cases, spouses have chosen the applicable law according to Article 5, by designating the law of their State of nationality. More frequently, absent a valid choice by the spouses, the law applicable to divorce or legal separation has been determined in accordance with Article 8: this usually leads to the application of the law of the country where the spouses are habitually resident, thereby promoting social integration and also restoring the correspondence between forum and jus.